Separation and purification of antioxidant peptides from purple speckled kidney bean by macroporous adsorption resin and analysis of amino acid composition - Li, Dan; Xu, Xin-yu; Yang, Yang; Wu, Na; Ma, Zhan-qian; Zuo, Feng; Zhang, Na (Frontiers in Nutrition, 2022)
The protein hydrolysate of purple speckled kidney bean (PSKB) was used as the raw material in this study, the antioxidant peptide of the PSKB protein hydrolysate was purified by macroporous resin. XAD-7HP macroporous resin was selected as the best purification material, and the static adsorption-desorption of the purified PSKB antioxidant peptide was optimized. The optimum static adsorption and desorption conditions were as follows: the adsorption capacity can reach to 11.85 mg/mL at pH 7 for 24 h and the desorption capacity was 5.15 mg/mL with 60% ethanol for 30 min. Under this condition, the amount of antioxidant peptide obtained by adsorption-desorption was the most. The optimum process conditions were as follows: the appropriate flow rate was 1 mL/min, and the optimal injection volume was 40 mL. The adsorption amount at this time can reach to 13.25 mg/mL. The components with elution time of 10 30 min were separated by RP-HPLC technique to obtain three main components RP1, RP2 and RP3. The DPPH free radical scavenging ability reached to 56.26%, 66.42% and 78.57% respectively, which were 36.65%, 46.34%, and 54.39% higher than those before purification. The amino acid sequences of the three components were identified as Phe-Leu-Val-Asp-Arg-Ile, Phe-Leu-Val-Ala-Pro-Asp-Asp and Lys-Asp-Arg-Val-Ile-Ser-Glu-Leu.